British ancestery and ancient (Israelites British Israel) - KHELIFI, Fatima Zohra (My University, 2017)
By the early of the 17th century Europe saw the rise of many movements and cults. The so called British- Israel or Anglo Israelism is one of these cults which in its function aims to identify Britain and the British Nation identity with Israel. In other words, the first inhabitants of the British Isles (the Celtic and Anglo Saxons) are considered the descendants of the Israelite tribes. Thus, this thesis sheds lights on the British Israel by representing its functions and aims. But this required a wide range of researches to sort with obvious information and brought clear evidence about it. Moreover, it depicts the historical and cultural contexts briefly of both British peoples and Israelites. The first part of this research paper depicts the origins and ancestry of the Celtic and Saxons peoples while the second part deals with the roots and ancestry of ancient Israel. Finally, according to many records this thesis concludes that the British- Israel is not fact. It is just a lie. It is no more than a myth.
Keywords: British Israelites; Britain; Israel; British identity; Celtic; Anglo-Saxons; British Isles; Ancient Israel